The Potential Role of Fosfomycin in Neonatal Sepsis Caused by Multidrug-Resistant Bacteria - Li, Grace; Standing, Joseph F.; Bielicki, Julia; Hope, William; van den Anker, John; Heath, Paul T.; Sharland, Mike (Drugs (New York, N.Y.), 2017)
The broad-spectrum activity of fosfomycin, including against multidrug-resistant (MDR) strains, has led to renewed interest in its use in recent years. Neonatal sepsis remains a substantial cause of morbidity and mortality at a global level, with evidence that MDR bacteria play an increasing role. The evidence for use of fosfomycin in neonatal subjects is limited. We summarise current knowledge of the pharmacokinetics and clinical outcomes for the use of fosfomycin in neonatal sepsis and issues specific to neonatal physiology. While fosfomycin has a broad range of coverage, we evaluate the extent to which it may be effective against MDR bacteria in a neonatal setting, in light of recent evidence suggesting it to be most effective when administered in combination with other antibiotics. Given the urgency of clinical demand for treatment of MDR bacterial sepsis, we outline directions for further work, including the need for future clinical trials in this at-risk population.